158k views
0 votes
PLEASEEEEEEEEEE HELP ASAP PLEASEEEEEEEEEE

PLEASEEEEEEEEEE HELP ASAP PLEASEEEEEEEEEE-example-1
User Chb
by
5.5k points

2 Answers

5 votes

We start with


(4m^(-3)n^(-2))/(m^(-1)n)

Simplifying the exponents, we have


(4m^(-3)n^(-2))/(m^(-1)n) = 4m^(-3)n^(-2) (mn^(-1)) = 4m^(-3+1)n^(-2-1)=4m^(-2)n^(-3)

So, the exponents are ok.

If we plug the values, we have


4m^(-2)n^(-3) \mapsto 4(-2)^(-2)(4)^(-3) = 4\cdot (1)/((-2)^2)\cdot(1)/(4^3) = 4\cdot (1)/(4)\cdot (1)/(64) = (1)/(64)

So, she didn't apply the exponent -2 correctly.

User Benlumley
by
5.4k points
6 votes

Answer:

3rd choice

Explanation:

In division for variables with same base, you do subtract top exponent minus bottom exponent. She did that correctly since -3-(-1)=-3+1=-2 and -2-1=-3.

The problem said m=-2 and n=4 and she replace m with (-2) and n with (4). She did this correctly.

You can multiply base numbers unless the exponents are the same 4 doesn't have the exponent -2 on it so you can't do (4(-2))^(-2)

The error is the 3rd option.

User Santhosh Divakar
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.